LABEL-FREE AND PROTEIN G-ENHANCED OPTICAL FIBER BIOSENSOR FOR DETECTION OF ALDH1A1 CANCER BIOMARKER - Yegizbay, Zhandos (Nazarbayev University School of Sciences and Humanities, 2025)
Cancer remains one of the leading causes of morbidity and mortality worldwide, highlighting the need for improved early detection strategies. Aldehyde dehydrogenase 1A1 (ALDH1A1) has emerged as a significant biomarker associated with tumor progression, chemoresistance, and poor prognosis in various cancers, including breast, lung, colorectal, prostate, and lymphoma. Current diagnostic methods for ALDH1A1, such as flow cytometry and ELISA, are limited by long detection times, the need for labeling, and reduced sensitivity in complex biological matrices. This study presents a novel optical fiber biosensor based on magnesium silicate nanoparticle-doped fibers for the label-free detection of ALDH1A1. The biosensor design incorporated protein G for enhanced antibody orientation and binding efficiency and anti-ALDH1A1 antibodies for specific recognition. Several sensor configurations were fabricated using a semi-distributed interferometer (SDI) format, and their performance was evaluated across a wide concentration range (10 fM–100 nM) in both phosphate-buffered saline (PBS) and fetal bovine serum (FBS). Our findings demonstrated that the inclusion of protein G significantly improved sensor sensitivity and reproducibility, achieving a limit of detection (LoD) of 172 fM in PBS. The sensor also maintained a positive response trend in FBS, indicating its potential applicability in clinically relevant samples. Furthermore, specificity testing confirmed the sensor's selectivity toward ALDH1A1, with negligible response to vascular endothelial growth factor (VEGF). This work introduces the first reported optical fiber biosensor for ALDH1A1 detection, offering a rapid, label-free, and highly sensitive approach suitable for future development in cancer diagnostics.
Keywords: Type of access: Embargo; ALDH1A1; Optical biosensor; Cancer biomarker detection; Nanoparticle